Euphemism Used in Oline CNN Indonesia News - Falizca Syaharani; Refnaldi Refnaldi (English Language and Literature, 2022)
This study aimed to find out the forms of euphemism used in online CNN Indonesia news. The data were taken from 20 random articles of CNN Indonesia in 2021. In this study, the theory of forms of euphemism was introduced by Werren (1992). The study used qualitative research. The result of this study found 69 data forms of euphemism. There were 12 forms, namely: compounding, derivation, acronym, slang, abbreviation, loan word, particularization, implication, metaphor, metonymy, litotes, hyperbola. By the finding, it can be concluded that the form of euphemism used in online CNN Indonesia news dominantly is loan word (24,63%). There were four forms not found in CNN Indonesia, which are blending, onomatopeia, phonemic replacement, and irony.